2009
DOI: 10.1097/prs.0b013e318195661a
|View full text |Cite
|
Sign up to set email alerts
|

Single Sutural Craniosynostoses: Surgical Outcomes and Long-Term Growth

Abstract: Treatment of single sutural synostosis was extremely safe with very low reoperative rates, but subsequent calvarial growth was abnormal, with a tendency toward recapitulation of the primary deformity. Growth was less diminished in procedures performed in older infants. Surgeons treating single sutural craniosynostosis should consider expanding treatment goals beyond normalization to an overcorrection of the abnormal skull shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 23 publications
5
116
1
Order By: Relevance
“…2,4,6,12,15,18,22,23,[29][30][31][32]36,39,40,46,51 The decrease in CI that we observed over time is comparable to the limited available data on long-term outcome. 2,16 Adding a widening bridge complies with Fearon and colleagues' suggestion to overcorrect width to compensate for later growth restriction in that direction.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…2,4,6,12,15,18,22,23,[29][30][31][32]36,39,40,46,51 The decrease in CI that we observed over time is comparable to the limited available data on long-term outcome. 2,16 Adding a widening bridge complies with Fearon and colleagues' suggestion to overcorrect width to compensate for later growth restriction in that direction.…”
Section: Discussionmentioning
confidence: 90%
“…Aesthetic results tend to decrease over time, as shown in several studies. 2,15,16 This phenomenon seems to occur regardless of the timing and extensiveness of the surgical correction. Moreover, the risk of developing increased ICP remains after remodeling.…”
mentioning
confidence: 99%
“…On the one hand, FOA is a standardized and well-established surgical technique, which allows the abnormally closed suture to be opened and movement of the affected bone segments in the desired direction (Aryan et al, 2005;Fearon et al, 2009). On the other hand, FOA is usually accompanied with substantial blood loss and the need for RBC transfusion due to the infant's low circulating blood volume (Maugans et al, 2011;Oppenheimer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether longer follow-up would uncover some anatomical differences, as it has previously been shown that the original dysmorphology may return. 3,22 It would be interesting to see if patients with neosutures have improved cranial morphology in the long term. Certainly, further studies must be carried out to better characterize the neosutures with a longer-term follow-up and with a larger sample size.…”
Section: 11mentioning
confidence: 99%